2013
DOI: 10.4103/0970-9185.119158
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal sufentanil or fentanyl as adjuvants to low dose bupivacaine in endoscopic urological procedures

Abstract: Context:Opioids are being increasingly used these days as adjuvants to local anesthetics in spinal anesthesia.Aim:The aim of this study is to compare the effects of adding sufentanil or fentanyl to low dose bupivacaine in spinal anesthesia for endoscopic urological procedures.Settings and Design:Prospective, randomized, double-blind study.Materials and Methods:A total of 90 elective endoscopic urological surgery patients, 40-80 years old, received spinal anesthesia with 7.5 mg hyperbaric bupivacaine 0.5% (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The 2 groups showed the same efficacy of spinal block by measuring and comparing the levels of anesthesia, analgesia and motor blockade. Our results are compatible with those from the study done by Gupta et al 17 The Gupta et al 17 study found 13.0% of hypotension in group B. However, there was no hypotension found in Group F. This was different from our study, as hypotension was found in 12.9% of patients in group F. The dose of fentanyl 25 mcg, administered intrathecally, may be too high for Thai people.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The 2 groups showed the same efficacy of spinal block by measuring and comparing the levels of anesthesia, analgesia and motor blockade. Our results are compatible with those from the study done by Gupta et al 17 The Gupta et al 17 study found 13.0% of hypotension in group B. However, there was no hypotension found in Group F. This was different from our study, as hypotension was found in 12.9% of patients in group F. The dose of fentanyl 25 mcg, administered intrathecally, may be too high for Thai people.…”
Section: Discussionsupporting
confidence: 76%
“…Elderly patients may be more susceptible to sustained hypotension in comparison to younger patients, in so saying, Gupta et al's 17 patients' age were 62.9 years of age on average. Gupta et al 17 found that group B had 3.3% of bradycardia. Group F had 3.3% of pruritus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[5][6][7][8][9] Given increasing demand for effective, low-dose neuraxial techniques, selection of intrathecal opioid has been the topic of several recent studies. [10][11][12][13] Fentanyl and sufentanil are lipophilic opioids with similar chemical structure and intrathecal pharmacokinetics. 14 They exhibit structural similarities to local anesthetics and exert an effect on sensory C afferent nerve fibers.…”
mentioning
confidence: 99%
“…Through searching in databases and screening with preset criteria, a total of twelve studies [6][7][8][11][12][13][14][15][16][17][18][19] were included for following a meta-analysis. The search process was described in Figure 1.…”
Section: Selection Of Trialsmentioning
confidence: 99%